Prevalence and factors associated with cognitive impairment in Chinese heart failure patients: A pilot study - Niu, Qi; Liu, WeiHua; Wang, FengLing; Dong, YanHong (Frontiers in Cardiovascular Medicine, 2022)
Background: The prevalence of Cognitive impairment (CI) is high in patients with heart failure (HF). It leads to poor prognosis, such as self-care, hospital readmission and increased mortality. However, such information among Chinese population is unclear. Objective: The purpose of this study was to examine the prevalence of CI in Chinese patients with HF, and explore its correlation with biomarkers and clinical factors to better manage HF patients with CI. Methods: This study is a cross-sectional study of 200 hospitalized HF patients in China. The cognitive function of HF patients was assessed by the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). Results: The majority are male (62.5%, n=125), have primary school and below level of education (57.5%, n=115), NYHA Ⅲ and above (62%, n=124). They have an average MoCA score of 15.10±8.18, MMSE score of 19.55±8.23. Age, NYHA class, and atrial fibrillation were independently associated with CI (p<0.05). There was a significant association between CI and the 4th quartile of TNT (p=0.013), and the 3rd and 4th quartile of NT-proBNP (p=0.015, p=0.038). Conclusions: The prevalence of undiagnosed CI in Chinese HF patients is high (81%). HF patients with high levels of TNT or NT-proBNP or both values may be at risk of developing CI. Therefore, we suggest that HF patients with older age, atrial fibrillation, NYHA class Ⅱ and Ⅲ, as well as elevated TNT or NT-proBNP or both values to be followed up with a formal evaluation for CI. Nurses need to provide targeted health education program for cognitively impaired HF population to improve their self-care ability and nursing outcome.